Diplomatische Wissenskulturen der Frühen Neuzeit Erfahrungsräume und Orte der Wissensproduktion - Braun, Guido (Bibliothek des Deutschen Historischen Instituts in Rom, 2018)
The methodology of cultural history opens new pathways for researching diplomatic figures and structures in the premodern era. However, until now, early modern knowledge cultures have not been researched in terms of their cultural impacts on diplomats and their role in producing knowledge. This volume examines this topic in the context of "spaces of experience" and "places of knowledge production" in early modern diplomacy.